White Bean Flour (Phaseolus vulgaris): Therapeutic and Toxicological Research in Wistar Rats - Luciana Lopes Silva Pereira, Chrystian Araujo Pereira, Raimundo Vicente de Sousa, Custodio Donizete dos Santos, Clarissa Ferreira de Moraes, Livia Cabral Satiro (Journal of Applied Pharmaceutical Science)
The objective was to evaluate the possible therapeutic and toxic effects resulting from administration of white bean flour (WBF) in Wistar rats for 21 days. The assay was performed to assess the consequences of using WBF crude, at a the concentration corresponding to the recommended daily dose to cause weight loss and hypoglycemic effect, which is 1,000 mg of phaseolamin/day. The administration of WBF at 1 mg/g body weight in Wistar rats with diabetes induced by STZ in a period of 21 days, did not alter physiological parameters (consumption of food and water, urine volume), biochemical markers (total cholesterol, HDL cholesterol and triglycerides), liver enzymes (gamma-GT, AST and ALT), and weight of organs (liver and pancreas) as well as fecal excretion of proteins and lipids. An increased excretion of carbohydrate fecal confirms the results of inhibition of α-amylase. Despite the tendency to decrease blood glucose from 20 days of treatment, there was no significant reduction during the period evaluated in the treated group. It can be concluded that despite the decreasing tendency of hyperglycemia and possibly aid in weight loss by decreasing absorption of carbohydrates in the diet, high doses of WBF may have deleterious effects on the body resulting from chronic use.
Keywords: Diabetes,phaseolamin,enzymatic inhibition,white bean flour.